In Vitro Callus Proliferation from Leaf Explants of Green Gram after In Situ UV-B Exposure - Rajendiran, K; Vidya, S; Arulmozhi, D (International Journal of Applied Sciences and Biotechnology, 2016)
Callus induction was tried with leaf explants (third leaf from top of canopy) harvested from in situ control and supplementary UV-B irradiated (UV-B = 2 hours daily @ 12.2 kJ m-2 d-1; ambient = 10 kJ m-2 d-1) three varieties of green gram viz. CO-8, NVL-585 and VAMBAN-2 to study their viability for germplam conservation. Callus induction occurred both in control and UV-B stressed NVL-585 leaf explants. VAMBAN-2 both in unstressed and UV-B stressed conditions did not initiate callus. Only control leaf explants from CO-8 proliferated callus. Callus of UV-B irradiated NVL-585 weighed less (51.28 %) than control. Parenchyma cells were smaller in callus inducted from in situ UV-B exposed NVL-585 leaf explants. The leaf explants from UV-B stressed NVL-585 varieties of green gram responded to in vitro callus proliferation making them fit for germplasm conservation for cultivating in UV-B elevated environment.Int J ApplSci Biotechnol, Vol 4(1): 82-91